Experimental investigation and theoretical study on bearing capacity of strong PVC-FRP confined concrete column-weak joint strengthened with core steel tube under axial loading. (15th February 2021) - Yu, Feng; Bu, Shuangshuang; Li, Dongang; Feng, Chaochao; Fang, Yuan
Highlights: The failure mode of the specimens under axial compression is found. The effect of several parameters on the bearing capacity and strains are revealed. The model for estimating the bearing capacity is proposed. The comparison between the experimental data and calculated results is made. Abstract: In order to investigate the mechanical performance of strong PVC-FRP confined concrete (PFCC) column-weak joint strengthened with core steel tube(CST), nine specimens are designed and tested under axial load. Four parameters including the length and steel ratio of CST, height and stirrup ratio of joint are considered. The results indicate that the crushing of the joint concrete dominates the destruction of the specimens. However, the lower and upper columns are not broken. With the increase of the stirrup ratio of joint, length or steel ratio of CST, or reduction of the height of joint, the yield and ultimate bearing capacity improves. The analysis of the strains shows that the longitudinal reinforcement, stirrups in the joint and CST yield. Based on the theory of the confined concrete and the limit equilibrium method, considering four affecting factors, a comprehensive influence coefficient φ is introduced. Whereafter, a theoretical predicting model for the axial strength of the strong PFCC column-weak RC beam joint strengthened with CST under axial compression is proposed. The verification results by this study and other research data show that the model has high accuracy.